Analysis The Effect of Green Computing on Green Satisfaction, Green Perceived Quality, and Green Trust on The Apple Consumer in Surabaya - Fania Cecillia; Rinabi Tanamal (SISFORMA, 2020)
The use of electronic devices such as smartphones has become a part of daily activities, it also led to the growing number of smartphones users as well as brands emerged. Smartphones can help humans, but it also can endanger the environment and living things, because electronic waste contains hazardous materials that can harm the environment. The implementation of green computing in IT companies can be one of the solutions for facing the electronic waste that keeps growing and one of the IT companies that already implemented it was Apple. This study aims to examine whether there is a positive influence of environmental friendliness created in the implementation of green computing to green satisfaction, green perceived quality, and green trust. The results showed that there is an influence given by the friendliness of the environment from the implementation of green computing on green satisfaction, green perceived quality and green trust with the highest correlation value, environmental friendliness towards green trust with a value of 0.644 which can be a consideration for IT companies.